MENINGKATKAN KEMAMPUAN SOSIAL ANAK USIA 5-6 TAHUN MELALUI BERMAIN PERAN DI TAMAN KANAK-KANAK ALIFIA SAMARINDA - Eniyawati; Arbayah; Sjamsir, Hasbi (BEduManagers Journal : Borneo Educational Management and Research Journal, 2022)
The background of the study is due to the lack of social skills of children in terms of mutual respect, mutual help and unwilling to join their groups. This is due to a lack of creativity or variety in delivering learning. The learning approach is important and determines the success or failure of the learning process. This approach can be done by playing. One method that can be used is through role playing. The design of this study is Classroom Action Research (PTK). The steps in this study are planning, implementation, observation, and reflection. The subjects of the study were 13 children of group B. The purpose of this study was to improve social skills through role play in Alifia Samarinda Kindergarten. Research data were obtained from the collection of instruments through RPPM, RPPH, teacher observation sheets, child observation sheets. Data analysis techniques with descriptive qualitative and quantitative. Indicators of aspects of achievement are mutual respect, caring and willing to help if asked for help, an attitude that can adjust. With the assessment category using a score of 1 Undeveloped (BB), score 2 Starting to Develop (MB), score 3 Developing as Expected (BSH) and score 4 Very Good Developing (BSB). The design of this study is Classroom Action Research (PTK). The steps in this study are planning, implementation, observation, and reflection. The subjects of the study were 13 children of group B. The purpose of this study was to improve social skills through role play in Alifia Samarinda Kindergarten. Research data were obtained from the collection of instruments through RPPM, RPPH, teacher observation sheets, child observation sheets. Data analysis techniques with descriptive qualitative and quantitative. Indicators of aspects of achievement are mutual respect, caring and willing to help if asked for help, an attitude that can adjust. With the assessment category using a score of 1 Undeveloped (BB), score 2 Starting to Develop (MB), score 3 Developing as Expected (BSH) and score 4 Very Good Developing (BSB).